Entrepreneurial Intention and Delayed Job Satisfaction From the Perspective of Emotional Interaction: The Mediating of Psychological Capital - Na, Boxiang; Ahmad, Noor Hazlina; Zhang, Chenxiao; Han, Yan (Frontiers in Psychology, 2022)
The coronavirus disease 2019 (COVID-19) pandemic has exacerbated the labour shortage, and promoting entrepreneurship to spur job creation is one of the most effective strategies to address this problem. Entrepreneurs must lengthen their employment or start-up cycles due to COVID-19 normalisation. Consequently, the impact of career willingness to delay satisfaction on entrepreneurial ambition is investigated in this research via an online survey in Jiangsu Province, China. The findings show that students with a high level of career delayed contentment has a higher level of entrepreneurial intention (EI), implying that career delayed contentment intention influences EI positively. Psychological capital (PC) modifies this process, increasing the influence of job delayed satisfaction on EI by strengthening PC. PC’s significant components are self-efficacy, hope, optimism, and flexibility. This study combines the willingness to wait for satisfaction with the willingness to start a business, providing a valuable reference for reducing the work condition caused by the COVID-19 epidemic.